Phase II Study of 5‐Fluorouracil, Oxaliplatin plus Dasatinib (FOLFOX‐D) in First‐Line Metastatic Pancreatic Adenocarcinoma. (23rd June 2021) - George, Thomas J.; Ali, Azka; Wang, Yu; Lee, Ji‐Hyun; Ivey, Alison M.; DeRemer, David; Daily, Karen C.; Allegra, Carmen J.; Hughes, Steven J.; Fan, Z. Hugh; Cameron, Miles E.; Judge, Andrew R.; et al.
Abstract: Lessons Learned: Preclinical studies have demonstrated that Src inhibition through dasatinib synergistically enhances the antitumor effects of oxaliplatin. In this phase II, single‐arm study, FOLFOX with dasatinib in previously untreated patients with mPC only showed only modest clinical activity, with a progressive‐free survival of 4 months and overall survival of 10.6 months. Continued investigation is ongoing to better understand the role of Src inhibition with concurrent 5‐fluorouracil and oxaliplatin in a subset of exceptional responders. Background: Src tyrosine kinase activity is overexpressed in many human cancers, including metastatic pancreatic cancer (mPC). Dasatinib is a potent inhibitor of Src family of tyrosine kinases. This study was designed to investigate whether dasatinib can synergistically enhance antitumor effects of FOLFOX regimen (FOLFOX‐D). Methods: In this single‐arm, phase II study, previously untreated patients received dasatinib 150 mg oral daily on days 1–14, oxaliplatin 85 mg/m 2 intravenous (IV) on day 1 every 14 days, leucovorin (LV) 400 mg/m 2 IV on day 1 every 14 days, 5‐fluorouracil (5‐FU) bolus 400 mg/m 2 on day 1 every 14 days, and 5‐FU continuous infusion 2, 400 mg/m 2 on day 1 every 14 days. Primary endpoint was progression‐free survival (PFS) with preplanned comparison to historical controls. Results: Forty‐four patients enrolled with an estimated median PFS of 4.0 (95% confidence interval [CI], 2.3–8.5) months and overall survival (OS) of 10.6 (95% CI, 6.9–12.7) months. Overall response rate (ORR) was 22.7% ( n = 10): one patient (2.3%) with complete response (CR) and nine patients (20.5%) with partial response (PR). Fifteen patients (34.1%) had stable disease (SD). Nausea was the most common adverse event (AE) seen in 35 patients (79.5%). Conclusion: The addition of dasatinib did not appear to add incremental clinical benefit to FOLFOX in untreated patients with mPC.